Analysis and measurement of the impact of some fiscal policy indicators on the general budget deficit in Iraq for the period (2004-2021) (Eurasian Journal of History, Geography and Economics, 2023)
Fiscal policy occupies an important place among the economic policies of all countries, regardless of their nature, philosophy, and economic systems, because of its vital and effective role in influencing macroeconomic changes through its various tools used to address various economic problems, including the most important of which is the problem of the general budget deficit, as it is considered among the most important economic problems. The centrality that has direct effects on the economic performance of developing countries and Iraq among them, especially in recent years, after taking the path of deficit in general tends towards increasing and what follows from the increasing negative effects of its means of financing, including high indebtedness, and accordingly, the study aims to identify the most important policy indicators Finance that directly affects the determination of the public budget deficit, and a statement of the impact of those indicators in containing or mitigating the public budget deficit in Iraq